Pemanfaatan Digital Marketing Bagi Usaha Mikro Kecil Dan Menengah Pada Era Ekonomi Asean - Rahaman, Nito Fathur (Jurusan Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jenderal Soedirman, 2024)
Abstract: Today's technology continues to grow and the benefits of using the internet are felt for the users. Some people feel dependent on the existence of the internet, including the activities of Micro, Small and Medium Enterprises (SMEs) in utilizing information technology to run their business, especially in the era of the ASEAN Economic Community (AEC). The purpose of this research is to generally describe the impact of digital marketing on sales volume for MSEs in the city of Jakarta. This research is of a qualitative type, using a triangulation model, which combines structured interview methods, in-depth interviews and observations of MSME actors who are actively registered at the Office of Market Community Empowerment – Cooperatives and City Small and Medium Enterprises. From the research results it is known that digital marketing makes it easier for MSME players to provide information and interact directly with consumers, expand market share, increase awareness and increase sales for UKM players. Keywords: digital marketing communiacation, umkm,marketing management